Sox10 contributes to the balance of fate choice in dorsal root ganglion progenitors. - Mariana Delfino-Machín; Romain Madelaine; Giorgia Busolin; Masataka Nikaido; Sarah Colanesi; Karen Camargo-Sosa; Edward W P Law; Stefano Toppo; Patrick Blader; Natascia Tiso; Robert N Kelsh (PLoS ONE)
The development of functional peripheral ganglia requires a balance of specification of both neuronal and glial components. In the developing dorsal root ganglia (DRGs), these components form from partially-restricted bipotent neuroglial precursors derived from the neural crest. Work in mouse and chick has identified several factors, including Delta/Notch signaling, required for specification of a balance of these components. We have previously shown in zebrafish that the Sry-related HMG domain transcription factor, Sox10, plays an unexpected, but crucial, role in sensory neuron fate specification in vivo. In the same study we described a novel Sox10 mutant allele, sox10baz1, in which sensory neuron numbers are elevated above those of wild-types. Here we investigate the origin of this neurogenic phenotype. We demonstrate that the supernumerary neurons are sensory neurons, and that enteric and sympathetic neurons are almost absent just as in classical sox10 null alleles; peripheral glial development is also severely abrogated in a manner similar to other sox10 mutant alleles. Examination of proliferation and apoptosis in the developing DRG reveals very low levels of both processes in wild-type and sox10baz1, excluding changes in the balance of these as an explanation for the overproduction of sensory neurons. Using chemical inhibition of Delta-Notch-Notch signaling we demonstrate that in embryonic zebrafish, as in mouse and chick, lateral inhibition during the phase of trunk DRG development is required to achieve a balance between glial and neuronal numbers. Importantly, however, we show that this mechanism is insufficient to explain quantitative aspects of the baz1 phenotype. The Sox10(baz1) protein shows a single amino acid substitution in the DNA binding HMG domain; structural analysis indicates that this change is likely to result in reduced flexibility in the HMG domain, consistent with sequence-specific modification of Sox10 binding to DNA. Unlike other Sox10 mutant proteins, Sox10(baz1) retains an ability to drive neurogenin1 transcription. We show that overexpression of neurogenin1 is sufficient to produce supernumerary DRG sensory neurons in a wild-type background, and can rescue the sensory neuron phenotype of sox10 morphants in a manner closely resembling the baz1 phenotype. We conclude that an imbalance of neuronal and glial fate specification results from the Sox10(baz1) protein's unique ability to drive sensory neuron specification whilst failing to drive glial development. The sox10baz1 phenotype reveals for the first time that a Notch-dependent lateral inhibition mechanism is not sufficient to fully explain the balance of neurons and glia in the developing DRGs, and that a second Sox10-dependent mechanism is necessary. Sox10 is thus a key transcription factor in achieving the balance of sensory neuronal and glial fates.